2016
DOI: 10.1007/s11664-016-4843-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Tube Super-Dielectric Material Hypothesis: Increased Energy Density Using NaCl

Abstract: The focus of the present work is the evaluation of the low-frequency dielectric performance of titanium dioxide nanotube arrays, created by anodization, filled with aqueous NaCl solutions. At low frequency (ca. <10 À2 Hz), capacitors made up of this so-called tube super-dielectric material were found to have extreme dielectric constants, greater than 1 billion. The same capacitors also registered unprecedented energy densities, nearly 400 J/cm 3 , better than that observed (<250 J/cm 3 ) for the same type of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…In fact, in this and earlier studies, it was found that the capacitance is a function of voltage, leading to 'irregular wave forms' [8][9][10][11][12][13]. As discussed in earlier work, this indicates that the capacitance is voltage dependent, specifically decreasing as voltage increases.…”
Section: Electrical Measurementsupporting
confidence: 61%
See 4 more Smart Citations
“…In fact, in this and earlier studies, it was found that the capacitance is a function of voltage, leading to 'irregular wave forms' [8][9][10][11][12][13]. As discussed in earlier work, this indicates that the capacitance is voltage dependent, specifically decreasing as voltage increases.…”
Section: Electrical Measurementsupporting
confidence: 61%
“…0.05 mm thick, were anodized, as described elsewhere [8,9,[21][22][23], in an ethylene glycol solution containing small quantities of ammonium fluoride (0.25% w/w) and water (2.75% w/w), using a titanium cathode (2 cm distant from the anode) at a constant DC voltage of 40 V for 46 min. This process created a layer of cylindrical hollow titania tubes on the parent titanium, average length measured to be 7.7+/−0.4 μm [24], but for purposes of conservative computation of energy density and all other parameters, assumed to be 8 μm in length.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations